Excisional Debridement for Chronic Achilles Insertional Tendinosis: Technique and Case Series. Issue 4 (22nd October 2020) - Gaston, Tara E.; Skibicki, Hope; Chapter, Megan C.; Cheesman, Quincy; Daniel, Joseph N.
Category: Sports; Ankle Introduction/Purpose: Operative treatment of chronic Achilles insertional tendinosis (AIT) involves tendon debridement, removal of the retrocalcaneal bursitis, and excision of the calcaneal exostosis, often followed by repair of the Achilles tendon and deep tendon transfer. The literature describes a variety of techniques without a single standard of care. The purpose of this study is to describe a novel approach for the treatment of chronic AIT and report clinical outcomes and complications of this technique. Methods: A retrospective review was performed of 57 patients with chronic AIT who were treated with the proposed surgical technique by a single surgeon from January 2015 through January 2019. Patient demographics, pain scores, functional outcome scores, and complications were reviewed. A telephone survey was also utilized to assess patient satisfaction. Following the breakdown of the data, comparisons of the preoperative scores were compared to the postoperative outcomes using Mann- Whitney U testing. Results: Preoperative VAS pain scores and VR-12 Physical scores were significantly improved at two year follow up. Additionally, patients described the outcome of their surgery as, 'very good.' Complications were also few and minimal. Three (5.3%) patients experienced superficial skin breakdown requiring return to the operating room and three (5.3%) developed postoperative cellulitis which responded to local care and oral antibiotics. There were no ruptures or record of recurrence of disease or pain. Conclusion: The technique described in this paper utilizes an excisional debridement of the central portion of the Achilles tendon in the shape of an apex superior triangle and therefore, does not require detachment of the tendon from its insertion on the calcaneus (Image 1). Functional outcome scores and pain significantly improved at two years follow up. Postoperative complications were similar to those previously reported with superficial wound breakdown being the most common. In conclusion, the authors encourage the use of this reliable, reproducible, and effective technique for the treatment of patients with chronic AIT.